2016
DOI: 10.1007/s00520-016-3244-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the risk factors associated with high-dose chemotherapy-induced dysgeusia in patients undergoing autologous hematopoietic stem cell transplantation: possible usefulness of cryotherapy in dysgeusia prevention

Abstract: Our study showed that dysgeusia after AHSCT led to the decrease in oral intake and extended the TPN administration period. Moreover, MEAM or LEED chemotherapy and oral mucositis were independent risk factors for dysgeusia in patients undergoing AHSCT, while oral cryotherapy was an independent suppressive factor for dysgeusia. Therefore, oral cryotherapy should be implemented into the regimen of supportive care management in patients undergoing AHSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
1
26
1
4
Order By: Relevance
“…Taste alterations, such as chemotherapy-induced oral mucositis, were found to be related to dysgeusia. [1,27] The present study showed higher taste alterations in patients with nausea, vomiting, loss of appetite and mucositis, corroborating previous studies.…”
Section: Characteristics Of Taste Alterationsupporting
confidence: 92%
See 4 more Smart Citations
“…Taste alterations, such as chemotherapy-induced oral mucositis, were found to be related to dysgeusia. [1,27] The present study showed higher taste alterations in patients with nausea, vomiting, loss of appetite and mucositis, corroborating previous studies.…”
Section: Characteristics Of Taste Alterationsupporting
confidence: 92%
“…Chemotherapy-induced oral mucositis causes deterioration of taste receptors. [1] Patients with oral mucositis are more likely to experience overall taste alterations, and to encounter problems, such as nausea and vomiting, changes in the sense of smell, difficulty in eating hot food/fatty food/meat, and loss of appetite, due to these alterations. Taste alterations, such as chemotherapy-induced oral mucositis, were found to be related to dysgeusia.…”
Section: Characteristics Of Taste Alterationmentioning
confidence: 99%
See 3 more Smart Citations